Enhancing Elementary Students’ Understanding of Fractions Through the Application of the Teams Games Tournament Cooperative Learning Model - Royani, Tatu Maftuhah; Rochmat, Rochmat; Farhan, Yosep (Journal of Social Studies Arts and Humanities (JSSAH), 2024)
Mathematics is a fundamental subject in primary education that cultivates logical, analytical, and problem-solving skills. However, the topic of fractions is often perceived as complex by elementary students due to its abstract conceptual nature. This study aims to investigate the effectiveness of the Teams Games Tournament (TGT) cooperative learning model in enhancing students’ conceptual understanding and learning outcomes in fraction lessons. The research employed a classroom action research (CAR) design involving 18 second-grade students at SDS Islam Nurul Iman. Data were collected through individual tests, classroom observations, and reflection cycles conducted over two learning cycles. The implementation of the TGT model, which integrates group collaboration and academic competition, resulted in a significant improvement in students’ learning outcomes. The proportion of students achieving mastery increased from 44% in the pre-cycle to 83% after the second cycle, with a mean score improvement from 64 to 85. These findings demonstrate that the TGT model fosters active participation, motivation, and peer collaboration, contributing to deeper conceptual understanding of fractions. The study concludes that incorporating cooperative and game-based learning strategies like TGT can effectively enhance mathematics achievement and engagement in early-grade learners.